Parental homework-help profiles throughout grades 6 – 9: Relations to motivation and mathematics skills - Kikas, Eve; Mädamürk, Kaja; Silinskas, Gintautas (Frontiers in Education, 2022)
This study aimed to examine how parental profiles of supportive and controlling help during mathematics homework in Grades 6 and 9 change over time and relate to children’s mathematics-related motivation and skills. Participants included 719 mother–child dyads. Children’s perceptions of parental help and mathematics skills were assessed in both grades; children’s mathematics-related self-concept, interest, and mother-rated task persistence were assessed in Grade 6. Three similar profiles appeared in both grades. Average support and control profile included around 60%, Average support, high control profile 29–33%, and Low support, average control profile 11% of mothers and children. Profiles differed based on children’s self-concept, task persistence, and mathematics skills in Grade 6. Transitions of parental homework help predicted children’s mathematics skills in Grade 9. Findings show that children perceive parental homework help to different extent as supportive and controlling and different help profiles distinctively relate to the child’s motivation and skills.